Mittlere Schwingungsamplituden des ClO2F2−-Anions - Baran, Enrique José (1976)
The mean amplitudes of vibration of the ClO2F2− anion have been calculated using known spectroscopic data. The results are briefly discussed and comparisons are made with other species containing Cl−O and Cl−F bonds.